2006
DOI: 10.1016/j.jmb.2006.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Aart, a Designed Six-finger Zinc Finger Peptide, Bound to DNA

Abstract: Summary (150 words, 150 allowed)Cys2-His2 zinc fingers are one of the most common types of DNA-binding domains.Modifications to zinc-finger binding specificity have recently enabled custom DNA-binding proteins to be designed to a wide array of target sequences. We present here a 1.96 Å structure of Aart, a designed six-zinc finger protein, bound to a consensus DNA target site. This is the first structure of a designed protein with six fingers, and was intended to provide insights into the unusual affinity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 53 publications
1
62
0
Order By: Relevance
“…Although it is well known that amino acid positions À1, 3, and 6 within the recognition helix directly contact the DNA triplet, positions À2, 1, and 5 are also described as playing a role in binding to the phosphate backbone. 34 Our study suggests that serine at position À2 and arginine at position 6 are very important in binding to the phosphate DNA backbone and 5 0 -nucleotide, respectively. However, the roles of demonstrated that a transcriptional repressor protein, namely KRAB-HLTR3, was able to achieve 100-fold repression of transcription from the HIV-1 promoter.…”
Section: Discussionmentioning
confidence: 67%
“…Although it is well known that amino acid positions À1, 3, and 6 within the recognition helix directly contact the DNA triplet, positions À2, 1, and 5 are also described as playing a role in binding to the phosphate backbone. 34 Our study suggests that serine at position À2 and arginine at position 6 are very important in binding to the phosphate DNA backbone and 5 0 -nucleotide, respectively. However, the roles of demonstrated that a transcriptional repressor protein, namely KRAB-HLTR3, was able to achieve 100-fold repression of transcription from the HIV-1 promoter.…”
Section: Discussionmentioning
confidence: 67%
“…GinC5 was generated by fusing a hyperactive catalytic domain of the Gin invertase to the C5 zinc finger protein. The composite structure shown here is derived from those of DNA-bound ␥␦ resolvase (12) and the Aart zinc finger protein (14).…”
Section: Figmentioning
confidence: 99%
“…These proteins are composed of a series of modular zinc finger domains that each bind specifically to 3 or 4 base pairs of DNA (14). Synthetic zinc finger DNA-binding proteins have been generated for many sequences, using several approaches (15)(16)(17).…”
mentioning
confidence: 99%
“…Since the structure of Snail1 had not been resolved, we could not anticipate the solvent-exposed basic residues in the carboxyl half of the protein. However, given that zinc fingers are structurally well conserved, we generated a threedimensional model of this part of the protein using the synthetic six-finger zinc finger Aart polypeptide bound to DNA as a template (Segal et al, 2006) (Fig. 2B).…”
Section: Characterization Of the Snail1 Nlsmentioning
confidence: 99%
“…The template used was the six-finger zinc finger Aart polypeptide bound to DNA (PDB code 2I13) (Segal et al, 2006). Raw structures obtained from fitting were subjected to steepest descent energy minimization and checked for packing errors.…”
Section: Modellingmentioning
confidence: 99%